Understanding elite rugby league players` experience of collision, effective contact coaching techniques, and player contact psychology: A focus group study - Dixon, A. J.; Littlewood, M. A.; Cronin, C. J.; Twist, C.; Close, G. L. (Journal of Sports Sciences, 2024)
The current study performed a series of online focus groups to understand elite rugby league players` experiences of collision. Eighteen rugby league players comprising different playing positions from four teams were recruited to participate in a series of online focus groups, via the Microsoft Team`s platform, facilitated by a moderator. Players were competing in Europe`s elite rugby league competition, the European Super League (ESL), during the 2021 season. All focus group data were transcribed, coded and analysed using reflexive thematic analysis guide to ensure robust exploring, interpreting and reporting through pattern-based analysis. The findings are split into five key themes: 1) the three-man tackle - the perceived optimal defensive strategy with simultaneous contact, 2) not all collisions are the same; matchplay events change the collision intensity, 3) bracing and blindsiding - two factors that influence experiences of collision and concussion, 4) coaching philosophies and orientations, 5) psychological readiness for collision. Collision sports have an inherent risk of injury; however, in some players` subjective experiences, there are collision types that have a greater association with risk or intensity (blind-sided collisions or long closing distances). It is essential that future research comprehends the effects of these collision types and the further themes.